Robust Surface Reconstruction Induced by Subsurface Ni/Li Antisites in Ni‐Rich Cathodes. (16th February 2021) - Li, Xinyan; Gao, Ang; Tang, Zhexin; Meng, Fanqi; Shang, Tongtong; Guo, Shengnan; Ding, Jiarun; Luo, Yanhong; Xiao, Dongdong; Wang, Xuefeng; Su, Dong; Zhang, Qinghua; et al.
Abstract: Loss of active materials is a critical problem of layered oxide cathodes for lithium‐ion batteries and undermines their long‐term electrochemical performance. However, the atomic‐scale outward migration mechanism of transition metals and oxygen remains elusive due to a highly localized environment at surface. Here, the robust surface reconstruction of LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) induced by artificially introduced Ni/Li antisites is reported. Using scanning transmission electron microscopy, the outward co‐migration process of nickel and oxygen ions is directly revealed at the atomic scale, finally resulting in a stable surface structure. The robust nature of this surface structure originates from the strong linear superexchange interaction between subsurface NiLi and surface Ni as supported by first‐principles calculations. An idealized subsurface structure with 1 3 NiLi is designed to suppress the outward migration of transition metal and oxygen ions and provide a universal lattice‐coherent surface protection strategy for layered lithium transition metal oxide cathodes. Abstract : Loss of active materials is a critical problem of layered oxide cathodes for lithium‐ion batteries and undermines their long‐term electrochemical performance. Using scanning transmission electron microscopy and first‐principles calculations, the outward Ni‐O co‐migration paths are demonstrated and a universal solution is provided: subsurface 1 3 Ni/Li antisites can stabilize the transition metals and oxygen at the surface by strong linear superexchange interaction.